Penerapan Posisi Quarter Prone Pada Pasien RDS (Respiratory Distress Syndrom) Terhadap Respiratory Rate dan Saturasi Oksigen Diruangan Nicu di Rumah Sakit Umum Daerah Prof. DR. H. Aloei Saboe Kota Gorontalo - Dewi Modjo; Muriyati Rokhani; Putri Ridwan Bakari (Malahayati Nursing Journal, 2024)
ABSTRACT Respiratory distress syndrome is the term used for respiratory dysfunction in neonates. This disease is associated with delayed development of lung maturity or inadequate amount of surfactant in the lung.This study aims to analyzeapplication of the quarter prone position in RDS (Respiratory distress syndrome) patients on respiratory rate and oxygen saturation in the nicu room at Prof. Dr. H. Aloei Saboe City of Gorontalo.This study uses quantitative research using a quasi-experimental design. The sample in this study were 3 baby respondents, the data collection technique was using observation sheets. The results showed that there were changes in respiratory rate and oxygen saturation in infants with respiratory distress syndrome after being given the quarter-prone position for 60 minutes. The conclusions in the study of applying the quarter prone position in RDS patients (respiratory distress syndrome)there were changes in respiratory rate and oxygen saturation before and after being held in the quarter prone position for 60 minutes. Keywords: Application, Quarter prone position, Respiratory Rate, Oxygen Saturation  ABSTRAK Respiratory distress syndrom adalah istilah yang digunakan untuk disfungsi pernafasan pada neonatus. Penyakit ini berhungan dengan keterlambatan perkembangan maturitas paru atau tidak adekuatnya jumlah surfaktan dalam paru. Penelitian ini bertujuan untuk menganalisis penerapan posisi quarter prone pada pasien RDS (Respiratory distress syndrom) terhadap respiratory rate dan saturasi oksigen diruangan nicu RS Umum Daerah Prof. Dr. H. Aloei Saboe Kota Gorontalo. penelitian ini menggunakan penelitian kuantitatif dengan menggunakan desain quasi eksperimen. Sampel dalam penelitian ini adalah 3 responden bayi, teknik pengumpulan data yakni menggunakan lembar observasi. Hasil penelitian menunjukkan terdapat perubahan respiratory rate dan saturasi oksigen pada bayi respiratory distress syndrom setelah diberikan posisi quarter prone selama 60 menit. Adapun kesimpulan dalam penelitian penerapan posisi quarter prone pada pasien RDS (Respiratory distress syndrom) terdapat perubahan respiratory rate dan saturasi oksigen sebelum dan sesudah dilakukan posisi quarter prone selama 60 menit. Kata Kunci: Penerapan, Posisi quarter prone, Respiratory Rate, Saturasi Oksigen